The Relationship between Prediabetes and Body Mass Index of Outpatients at Dr. Dody Sarjoto Hospital at Maros Regency, South Sulawesi, Indonesia - Junedi Sitorus1, Nurhaedar Jafar2, Ridwan Amiruddin3, Sukri Palutturi4, Veni Hadju2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: The prevalence of prediabetes is increasing worldwide. According to the International DiabetesFederation in 2016,6.7% of the world’s population lived with this condition and estimated to rise to 7.8%in 2040. In general, prediabetes is accompanied by excess body mass index. Therefore, the purpose of thisresearch was to determine the relationship between prediabetes and body mass index of outpatients in theinternal medicine polyclinic at Dr. Dody Sarjoto Hospital, Maros Regency, South Sulawesi.Method: This was an analytical research design with cross sectional approach, involving 143 prediabetespatients. Secondary data were obtained from the record books of the hospital and subjected to Chi Squaretest.Result: The highest number of prediabetes cases were within the age range of 40-50 years (58.7%), amongfemale (73.4%), patients with high school education (58.7%), and in 81.1% of patients with family historyof DM. Furthermore, the result of the Chi Square test was 0.041, greater than <0.05, indicating a relationshipbetween prediabetes and BMI.Conclusion: There was a relationship between the cases of prediabetes and BMI of outpatients at dr. DodySarjoto Hospital, Maros Regency, South Sulawesi